Impact of rule making in relation to disagreement on inheritance law in islamc jurisprudence case study in Selangor - Muhammad Bashir Hj. Salim; Wan Abdul Fatah Wan Ismail (Universiti Sains Islam Malaysia, 2024)
The propose of the study is to highlight the method of solving inheritance problem based on ijtihad of the prophet's companions and jurisprudence scholars based on their understanding of al-Qur'an and Sunnah. Their discussions have helped solved many disputes among muslims especially im cases of the method used in dividing the inheritance which were not really detailed out in the al-Qur'an or Sunnah. The outcome of the discussions among the muslim scholars have given a great impact in the administration of inheritance in Malaysia especially in the state of Selangor. This study adopts two types of methodology. Firstly, library research on fiqh rules and regulations based on the opinions of muslim scholars, case studies and the like. Secondly, collection of field study data through interviews with judges of Syariah Court, Syariah officers, land officers and others. The results showed that the disputes among the prophet's companions and Muslim scholars only involve smaller part of the basic rules and regulations. These disputes involve two parties: the Mazhab of Maliki, Shafei and Hanbali which center around the method adopted by Saidina Zaid ibn Thabit r.a while the Mazhab of Hanafi centers around the methods used by Abdullah ibn Abbas r.a. Generally, Malaysia and specially the Syariah Court of Selangor adopts the method of Shafei in resolving inheritance disputes. On top of that, the Shariah Court of Selangor is the only court which practices Wasiah Wajibah as stated in Enheritance Enactment of the State of Selangor.